Peningkatan Hasil Belajar melalui Penggunaan Media Audio-Visual dalam Meningkatkan Kemampuan Mendengarkan Bahasa Inggris Siswa Kelas VIII-D UPT SMP Negeri 1 Tellu Limpoe Kabupaten Sidenreng Rappang - Ismaeni (JURNAL ARMADA PENDIDIKAN, 2024)
Audio-visual media, such as video, audio and interactive multimedia, can help students understand language contexts better, improve memory and stimulate interest in learning. Therefore, this classroom action research aims to explore and apply the use of audio-visual media in improving the listening skills of students of class VIII-D UPT SMP Negeri 1 Tellu Limpoe, Sidenreng Rappang Regency. The research method used in this research is descriptive statistical analysis method. The data used in the research are primary and secondary data. Primary data is data obtained by providing an overview of the changes or progress that occurred after the application of audio-visual media in learning to listen to class VIII-D students. Secondary data is data obtained through intermediaries, such as through report books, statistical boards, etc. The results showed that the application of audio-visual media in English language learning, especially in listening skills, significantly improved students' learning achievement, along with the increase in students' formative scores. Student learning completeness increased from 65% in cycle I to 100% in cycle II. The use of audio visual media can also increase students' activeness and interest in English lessons, with students becoming active subjects in learning activities, creating a pleasant learning atmosphere, and strengthening students' roles in the learning process.